RIRISK FACTORS OF OCCIPITAL STROKE IN A TERTIARY EYE CENTER IN YOGYAKARTA, INDONESIA - Satyawati, Budhi Hartiwi; Hartono, Hartono; Mahayana, Indra Tri (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Occipital stroke involves the occipital lobe of the brain, which can impair the visual acuity in patients. Several risk factors have been proven as predisposing conditions for occipital stroke. This study investigates the risk factors for occipital stroke in tertiary eye center in Yogyakarta. Methods: The method of this study was cross-sectional research by analyzing secondary data from medical records of patients with occipital stroke hospitalized in Dr. Yap Eye Hospital, a tertiary eye center in Yogyakarta. Patients diagnosed with occipital stroke from January 2021 to December 2022 were included in this study. Demography, clinical data, and risk factors associated with occipital stroke were recorded. The descriptive statistic was performed to evaluate the risk factors for occipital stroke. Results: Sixty-one subjects were analyzed, comprised of 44 males (72%) and 17 females (28%). The majority of subjects within age ?45 years old (93%). The attack occurred during activity (n=54, 89%) and wake-up (n=7, 11%). The involvement right eye (n=8, 13%), left eye (n=9, 15%), and bilateral (n=44, 72%). Of 122 eyes, 74 had hemianopia (61%), 34 had quadranopia (28%), and 14 had bilateral hemianopia (11%). Twenty-nine subjects had right occipital stroke (48%), 25 subjects had left occipital stroke (41%), and seven subjects had bilateral occipital stroke (11%). Most subjects had one risk factor (n=29, 48%) and two risk factors (n=23, 38%). Eight subjects had three risk factors (13%), and only one subject had four risk factors (2%). Conclusion: Most risk factors of occipital stroke involve only single and double risk factors. Only a minority of subjects had multiple risk factors.